Formulation of Mandatory Task Algorithm Using Task Prioritization Technique - Hong S.G.K.; Ahmad A.; Chong A.T.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Robotics; Scheduling algorithms; Software agents; Analytical Hierarchy Process; goal; goal deliberation; Human intervention; mandatory task; Software agent technology; Task complexity; Task prioritization; Multi agent systems